1929 Mo. Laws 170 - (:unkn) unknown (My University, 1929)
Crimes and Punishment, Prohibiting the Sale, Delivery, Transportation, Possession, or Control of Machine Rifles, Machine Guns and Sub-machine Guns, and Providing Penalty for Violation of Law, §§ 1-2: Prohibited selling, delivering, transporting, and possessing a machine gun. Punishable by imprisonment of 2-30 years and/or fine up to $5,000.
Keywords: MACHINE GUN RESTRICTION